FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KESIAPAN KLINIK PRATAMA DALAM MENGHADAPI AKREDITASI DI KOTA SEMARANG - Falentine Lidya Telussa; Ayun Sriatmi; Sutopo Patria Jati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
In the 2019 all primary clinics are targeted to be included in JKN (Universal Health Coverage - UHC). Accreditation becomes a requirement of BPJS Health credentials. So it can be said that all primary clinics must be accredited. Until 2017, there is no accredited primary clinic. This happens because the clinic does not know about the existence of this policy so it has not been prepared. This study aims to analyze factors that related to primary clinic’s readiness in facing accreditation. The research type is quantitative research, cross sectional approach, and using Chi Square test. The samples are 63 primary clinic. The results showed that the variables related with primary clinic preparation for accreditation were relative advantage (p = 0.042). Unrelated variables were compatibility (p = 0.393), complexity (p = 1.000), ability to be tried (p = 0.649), and ability to be seen (p = 0.675). Primary clinic in Semarang City and The Committe of First Level Health Facility (FKTP) Accreditation is expected to hold a benchmarking between primary clinic and primary health center wich have had the accreditation so that can obtain the idea of the whole in accreditaion itself.